2021
DOI: 10.12973/eu-jer.10.1.261
|View full text |Cite
|
Sign up to set email alerts
|

Improving Higher Order Thinking Skills via Semi Second Life

Abstract: This study was conducted to determine the effectiveness of virtual laboratory based on semi second life (s-SL) on higher order thinking skills of general senior secondary school in chemistry learning process. The research design was adopted posttestonly design approach to a quasi-experimental. This study was conducted in the one of public general senior secondary school in 3T regions -Bangkalan City -one of the cities in East Java Province, Indonesia. There were 81 students in the grade 11 of natural science w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Reference Simulation content L C SP TP QL QT (Amin & Ikhsan, 2021) Chemical equilibrium C QT (Chang & Linn, 2013) Chemical thermal dynamics L QL QT (Chen, Chang, Lai & Tsai, 2014) Boyle's Law L C SP QL QT (Chien, Tsai, Chen, Chang & Chen, 2015) Boyle's Law L QT (Correia et al, 2019) Behavior of gases at a sub-microscopic level L SP QL QT (Davenport, Rafferty & Yaron, 2018) Solutions (the mole) L QT (Donnelly, O'Reilly & McGarr, 2013) Unspecified C TP QL QT (Gambari, Gbodi, Olakanmi & Abalaka, 2016) Periodicity and chemical equations L SP QL QT (Gambari, Kawu & Falode, 2018) Identification of cations L QT (Hale-Hanes, 2015) Acid-base reactivity L SP QL QT (Homer & Plass, 2014) Kinetic molecular theory and ideal gas law L QT (Karlsson, Ivarsson & Lindstrom, 2013) Gas solubility L SP TP QL (Lamb & Annetta, 2013) Mole, chemical equations and stoichiometry L SP QT (Levy, 2013) States of aggregation and phase change C QL QT (Olakanmi, 2015) Chemical reactions L QL QT (Osman & Lee, 2013) Electrochemistry L QT (Papadimitropoulos, Dalacosta & Pavlatou, 2021) Acids and bases (properties, Arrhenius theory and pH) L QT (Plass, Milne, Homer, Schwartz, Hayward, Jordan et al, 2012) Kinetic molecular theory L C QT (Pratidhina, Pujianto & Sumardi, 2019) Gas laws L QT (Ryoo, Bedell & Swearingen, 2018) Properties of matter and chemical reactions L QT (Smetana & Bell, 2014) Atomic By way of general results (Figure 3), it was found that 87% of the articles include an analysis of the effect that the use of simulations has on the learning of chemical concepts or models. 19% of the works set out to specifically analyze the development of student competences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference Simulation content L C SP TP QL QT (Amin & Ikhsan, 2021) Chemical equilibrium C QT (Chang & Linn, 2013) Chemical thermal dynamics L QL QT (Chen, Chang, Lai & Tsai, 2014) Boyle's Law L C SP QL QT (Chien, Tsai, Chen, Chang & Chen, 2015) Boyle's Law L QT (Correia et al, 2019) Behavior of gases at a sub-microscopic level L SP QL QT (Davenport, Rafferty & Yaron, 2018) Solutions (the mole) L QT (Donnelly, O'Reilly & McGarr, 2013) Unspecified C TP QL QT (Gambari, Gbodi, Olakanmi & Abalaka, 2016) Periodicity and chemical equations L SP QL QT (Gambari, Kawu & Falode, 2018) Identification of cations L QT (Hale-Hanes, 2015) Acid-base reactivity L SP QL QT (Homer & Plass, 2014) Kinetic molecular theory and ideal gas law L QT (Karlsson, Ivarsson & Lindstrom, 2013) Gas solubility L SP TP QL (Lamb & Annetta, 2013) Mole, chemical equations and stoichiometry L SP QT (Levy, 2013) States of aggregation and phase change C QL QT (Olakanmi, 2015) Chemical reactions L QL QT (Osman & Lee, 2013) Electrochemistry L QT (Papadimitropoulos, Dalacosta & Pavlatou, 2021) Acids and bases (properties, Arrhenius theory and pH) L QT (Plass, Milne, Homer, Schwartz, Hayward, Jordan et al, 2012) Kinetic molecular theory L C QT (Pratidhina, Pujianto & Sumardi, 2019) Gas laws L QT (Ryoo, Bedell & Swearingen, 2018) Properties of matter and chemical reactions L QT (Smetana & Bell, 2014) Atomic By way of general results (Figure 3), it was found that 87% of the articles include an analysis of the effect that the use of simulations has on the learning of chemical concepts or models. 19% of the works set out to specifically analyze the development of student competences.…”
Section: Resultsmentioning
confidence: 99%
“…The possibilities for interaction offered by simulations (Homer & Plass, 2014), and the possibility of repeating the experiments as many times as necessary, in a short time and at no additional cost (Amin & Ikhsan, 2021), are other characteristics identified as promoting learning. Udo and Etiubon (2011) recommend the use of virtual laboratories due to their powerful facilitating effect, since they make it possible to work in a dynamic interactive environment that facilitates the reformulation of knowledge and mastery of concepts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of VLabs in the learning process, particularly in mathematics, which ensures learner interaction, especially in practical experiments that are difficult to implement, confirming that scientific materials are closely related to technological innovations [9], [11], [13], [23], [24], [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher Order Thinking Skills (HOTS) is a very important ability for students to master in this 21st century. HOTS includes critical, logical, reflective, metacognitive, and creative thinking skills in dealing with complex problems (Amin &;Ikhsan, 2021;Razak et al,2021). With higher order thinking skills students can analyze incoming information, make generalizations or conclusions based on patterns found, to evaluate and create new ideas (Acharya, 2021;Putra et al, 2023;Anderson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%